A good marriage : a novel - McCreight, Kimberly (Harper, an imprint of HarperCollinsPublishers, 2020)
"When Amanda, the gorgeous wife of start-up millionaire Zach Grayson, is discovered dead at the bottom of the stairs in her stately Brooklyn brownstone, her husband is immediately fingered as the primary suspect. Zach calls Lizzie, his law school classmate, hoping their shared history will convince her to come to his aid. A former U.S. Attorney with no violent crime experience, Lizzie reluctantly agrees to represent him, though the two haven't seen each other in years. As she works to exonerate Zach, Lizzie is drawn into the privilege, passion, and excess churning beneath Park Slope, Brooklyn's idyllic, virtuous streets. It's a world that's completely foreign to Lizzie, but, if she's honest, also unexpectedly intriguing-particularly in light of the increasingly steep cost of keeping her own troubled marriage afloat. Zach's case proves less clear cut than Lizzie anticipated, though-especially after revelations surface about the racy party he and Amanda attended the night before she died. It's the event of the summer for wealthy Park Slope parents, a chance to blow off some steam while the kids are at camp, and it's all consensual, harmless fun. At least, that's the idea The novel pulses with the energy of a legal thriller and the emotional urgency of page-turning domestic suspense. As Lizzie unwinds the truth about that night, she learns that Amanda was hiding far more than the cold reality of her distant marriage, and that other couples in the neighborhood harbor dark secrets of their own. In the end, Lizzie must confront not only her own marriage, but what it means to have a good marriage in the first place, and the dangerous compromises some couples make-and the secrets they keep-in order to stay together"--